Mobility levels of acute medical patients: Is behavioural mapping comparable to accelerometry?. (April 2021) - Wu, Yizhou; Smits, Esther J; Window, Peter; Beningfield, Alice; Johnston, Venerina; McRae, Prue
Objective: To (1) determine agreement between behavioural mapping and accelerometry for measuring mobility levels in an acute medical inpatient setting and to (2) explore and compare the required resources and costs for both methods. Design: Observational cross-sectional study Setting: Tertiary referral teaching hospital in Brisbane, Australia. Subjects: Adult patients admitted to two acute medical wards. Main measures: Mobility levels were recorded by behavioural mapping, and thigh and chest-worn accelerometers (ActivPAL). The level of agreement between the two methods was evaluated using the Intraclass Correlation Coefficients for each mobility level (i.e. lying, sitting, upright, standing and walking). Results: Nineteen patients (10 male (53%); mean(SD) age of 72(14) years) were included in the agreement analysis. The Intraclass Correlation Coefficients were high for 'lying' (ICC = 0.87), 'sitting' (ICC = 0.84) and 'upright' (ICC = 0.93), indicating good to excellent agreement between the two methods. For these mobility levels, mean differences between the two methods were small (<2%), with large standard deviations (up to 18%). Agreement was poor for 'standing' (ICC = 0.00) and 'walking' (ICC = 0.35). Both methods were labour-intensive, with labour costs of A$1, 285/€798 (34 hours) for behavioural mapping and A$1, 055/€655 (28 hours) for accelerometry. No further costs were involved in behavioural mapping, but clinical backfill was required. Accelerometry involved a financial investment for accelerometers (A$11, 100/€6, 894 for 22 ActivPAL devices). Conclusion: Agreement between behavioural mapping and accelerometry was good for measuring 'lying', 'sitting' and 'upright', but poor for 'standing' and 'walking' in an acute inpatient setting. Both behavioural mapping and accelerometry were labour-intensive, with high costs for the accelerometry equipment.